Effectiveness of Baby Oil On Skin Integrity Disorders in Patients With Uremic Pruritus Due to Chronic Kidney Failure: Efektivitas Baby Oil Terhadap Gangguan Integritas Kulit Penderita Pruritus Uremik Akibat Gagal Ginjal Kronik - Sitohang, Nur Asnah; Sara Hotmauli Br Manullang, Evi (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Chronic renal failure is an abnormality of kidney function and structure, where the glomerular filtration rate is less than 60 mL/min/1.73 m² and there is kidney damage that lasts more than 3 months. Uremic pruritus is one of the most common skin disorders in patients with chronic renal failure disease, which disrupts the physical and mental health of patients. Although pruritus is not life-threatening, it causes sleep disturbances and affects patients' quality of life. The participant in this case study was only one person diagnosed with CKD. One of the non-pharmacological interventions that can be done by nurses to patients is Baby Oil Therapy by applying 3-5 ml of Baby Oil on itchy skin for 15 minutes (3 times a day) for 4 consecutive days. The instrument used to assess itch intensity is Visual Analogue Scale (VAS, range: 0-10). The results of the provision of Baby Oil therapy decreased Visual Analogue Scale which initially scored 6 after intervention for 4 days the VAS scale of pruritus itching dropped to 1-2, the skin looks more moist, not dry and rough, redness is reduced and complaints of waking up while sleeping at night because of itching have decreased. This case study aims to evaluate the effectiveness of Baby Oil therapy for uremic pruritus in patients with chronic renal failure. Suggestions for further case studies are to analyze the impact of Baby Oil therapy not only on pruritus, but also on aspects of the quality of life of CKD patients.